Implementation of Discipline Character Education at SMP Muhammadiyah 10 Sidoarjo During The Covid-19 Pandemic - Sofyanora Pravita Agustin; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The writing of scientific papers examines the various results of research activities with the preparation of systematic language concepts. The purpose of writing this research is to find out how the system of implementing or implementing disciplined character education at Muhammadiyah 10 Sidoarjo Middle School during the covid-19 pandemic. As well as knowing the development of learning that occurs in the school. The current conditions have had a wide impact, especially in the field of education. This makes it difficult for everyone to interact outside the home. Including students and teachers doing online learning or Distance Learning (PJJ). In an era like today, it requires all people to be able to master information and communication technology. Face-to-face implementation in schools is also not possible because the number of pandemics is increasing, making school activities based on online learning. The method used during the research is descriptive method with a qualitative approach. This approach can be used as a reference in research in the field such as in a school environment. Programs held in schools have the goal of achieving to advance the performance of the workforce or the schools involved and the surrounding community. In addition, there is an expectation that related schools will be established and developed programs that exist in the school to make schools that have superior character, are based on Islamic values and improve the quality of resources human resources who have moral, intellectual, healthy and professional excellence.